Language, Youth, and Cultural Identity: Study on the Inheritance of Javanese Speech Levels among Teenagers in Yogyakarta - Wulandari, Astri; Mulyana, Deddy; Hadisiwi, Purwanti; Rizal, Edwin (SCAD Independent, 2025)
This study aims to discover how Javanese speech levels are inherited and learned by teenagers in Kotabaru, Yogyakarta, as well as the role of families and schools in internalizing this cultural heritage. The study also investigates how teenagers in Yogyakarta use Javanese as a marker of their cultural identity. The Javanese language is used in daily interaction and communication by native Javanese speakers in Central Java, East Java, and Yogyakarta. This article used a qualitative method with an ethnography of communication approach. The authors collected data by conducting field observations and interviewing teenagers in Kotabaru as informants. This study found that the role of teachers at school is more dominant in the inheritance and understanding of Javanese speech levels to teenagers compared to the role of parents at home. The knowledge and skills of the Javanese speech level of teenagers in Yogyakarta mostly use “ngoko” Javanese in daily communication with people in the family and neighborhood. Despite experiencing difficulties in learning and using the Javanese speech level, teenagers in Yogyakarta still consider the Javanese speech level as a form of their cultural identity as Javanese. The process of inheritance and internalization of the Javanese language requires the involvement of family and community, in addition to schools, in shaping the significance of the Javanese language as a cultural identity.